Acoustic perceptions of vessel fitness in southern Africa. (September 2017) - Fowler, Kent D; Sandred, Örjan; Whiteway, Autumn
The acoustic properties of objects found in archaeological contexts have seen little attention because they are seldom found intact. Nevertheless, sound is quality of objects that is of tremendous significance during both their manufacture and use. In this article, the authors examine how the acoustic properties of ceramic vessels influence the perception of their fitness for use. Grounded in how sound cues correlate to visual, tactile and olfactory measures of vessel fitness in an ethnographic context, they focus on detecting perceptible sonic differences between damaged and undamaged vessels produced by Zulu and Swazi potters in southern Africa. The article demonstrates how sound is a key quality of vessel 'strength' that both potters and clientele use to gauge functional and social suitability. We show that studies of fabric characteristics, such as fissures and voids, in addition to fabric composition provide a means to infer the acoustic properties of archaeological pottery and evaluate the significance of sound in past valuations of vessel fitness. Archaeological discussions of materiality can explore how social valuations of vessel fitness are accessible through studies of the functional properties of ceramics that consider human sensory experience.